Phytochemical and antioxidant activities of methanolic extract of Lawsonia inermis L. Bark - Golwala, Dharmesh K.; Vaidya, Santosh Kumar; Patel, Timir B; Patel, Darpini S.; Dholwani, Kishor K. (Current Issues in Pharmacy and Medical Sciences, 2020)
Many diseases are associated with oxidative stress are caused by free radicals. Current research has been directed towards finding naturally occurring antioxidants of plant origin. The aim of the present study was to evaluate the in vitro antioxidant activities of methanolic extract of Lawsonia inermis L. bark (MELIB). The present study was carried out for determination of qualitative, quantitative phytochemical and in vitro antioxidant activity for scavenging of free radical DPPH, superoxide radical scavenging and lipid peroxidation. The bark extract is a rich source of secondary metabolites like flavonoids at a rutin equivalent 73.43±0.26%, polyphenol at a gallic acid equivalent 84.70±0.43%, tannins at a tannic acid equivalent 88.75±0.14% and terpenoids at a linalool equivalent 68.13±0.31. MELIB showed free radicals scavenging capacity by way of the DPPH method (6.93±0.51 to 62.63±0.10% inhibition), the superoxide radical scavenging method (1.82±0.41 to 57.11±0.18% inhibition) and the ferric chloride induced lipid peroxidation method (9.87±0.33 to 80.32±0.82% inhibition). The results obtained in the present study indicate that MELIB can be a potential source of natural antioxidants due to the presence of flavonoids, polyphenols, tannins and terpenoids.